Enhanced Photocatalytic Performance in Ag+‐Induced BiVO4/β‐Bi2O3 Heterojunctions. Issue 2 (7th December 2015) - Shan, Lianwei; Liu, Yuteng; Ma, Chengguo; Dong, Limin; Liu, Lizhu; Wu, Ze
Abstract: BiVO4 /β‐Bi2 O3 photocatalysts have been fabricated by a facile Ag doping route. The method involves the substitution of the lattice Bi 3+ ions in BiVO4 with dopant Ag + ions, and the supplanted Bi 3+ ions generate the β‐Bi2 O3 (tetragonal phase) under thermal treatment in air. TEM observations and XRD results confirm that BiVO4 and β‐Bi2 O3 coexist in the Ag‐doped BiVO4 . The diffuse‐reflectance spectroscopy (DRS) results demonstrate that all of the BiVO4 /β‐Bi2 O3 photocatalysts show enhanced absorption in the visible region between λ = 550 and 650 nm, and the absorption intensity increases as the Ag content increases. The experimental results reveal that these BiVO4 /β‐Bi2 O3 nanostructures exhibit much higher visible‐light photocatalytic activities than that of BiVO4 for the degradation of the model dye Rhodamine B (RhB) under visible‐light irradiation. The enhanced photocatalytic efficiencies are attributed to charge transfer between BiVO4 and β‐Bi2 O3, which significantly promotes the separation of the photogenerated electrons and holes and, therefore, enhances the photocatalytic properties of the heterojunction. Furthermore, the doped Ag ions might play an important role in this improvement. This approach is expected to be beneficial for the design and optimization of heterojunction photocatalysts. Abstract : Under the proper heat‐treatment conditions, Ag doping induces the formation of BiVO4 /β‐Bi2 O3 heterojunctions. The Bi ions are replaced by Ag ions, the Bi ions are extruded, and β‐Bi2 O3 forms. At the same time, oxygen vacancies are a byproduct of the formation of the BiVO4 /β‐Bi2 O3 heterojunction.